Weight Management : A Practitioner's Guide - Pearson, Dympna; Grace, Clare (Chichester, West Sussex ; Ames, Iowa : Wiley-Blackwell, 2012)
"An increasingly wide range of patients of different age, ethnicity and social background often combined with other clinical conditions such as diabetes, cardiovascular disease or osteoporosis now find themselves battling against obesity and many health professionals become frustrated, feeling ill-equipped to handle each unique case with the one-size-fits-all approach offered by the "eat less, exercise more" mantra. Weight Management: A Practitioner's Guide explains how effective evidence-based programmes structured in a manner addressing the key components of diet and physical activity integrated with a behavioural approach could offer the solution to the obesity epidemic. This exciting new book from renowned experts Dympna Pearson and Clare Grace provides practitioners and those studying to become practitioners and public health professionals with a much needed modern guide that clearly presents the latest evidence underpinning treatments and uses a step-wise approach to implementing programmes and building skills and confidence. Written with the express needs of practitioners and related health professionals at its core, this book will be a ready reference for those working in both acute and community settings throughout the different and demanding stages of the weight management process. A practical guide to tackling weight management -- Covers diet, exercise and behavioural therapy -- Written for health professionals, by health professionals -- Includes advice on continuity of care and handling group programmes"--
"An increasingly wide range of patients of different age, ethnicity and social background often combined with other clinical conditions such as diabetes, cardiovascular disease or osteoporosis now find themselves battling against obesity and many health professionals become frustrated, feeling ill-equipped to handle each unique case with the one-size-fits-all approach offered by the "eat less, exercise more" mantra. Weight Management: A Practitioners Guide explains how effective evidence-based programmes structured in a manner addressing the key components of diet and physical activity integrated with a behavioural approach could offer the solution to the obesity epidemic"--
Why treat obesity? -- Health professionals' attitudes towards obesity and its management -- Treatment options: the evidence for what works -- Preventing overweight and obesity -- Providing a person-centered weight management service -- Building a picture: the assessment -- Finding solutions: supporting patients to establish a solid foundation -- Next steps: continuing to develop expertise -- Staying on track: weight maintenance -- Getting the most out of brief contacts -- Evaluating individual weight-management interventions -- Common challenges and misconceptions.
Includes bibliographical references and index.
Print version record.
Keywords: Obesity -- Treatment; Reducing diets; Exercise therapy; HEALTH & FITNESS -- Nutrition; MEDICAL -- Endocrinology & Metabolism; MEDICAL -- Nutrition; Exercise therapy; Obesity -- Treatment; Reducing diets; Electronic books; Electronic books